1995
DOI: 10.1016/0375-9474(95)00358-8
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on Σ-nucleus dynamics from dirac phenomenology of Σ− atoms

Abstract: Strong interaction level shifts and widths in Σ − atoms are analyzed by using a Σ nucleus optical potential constructed within the relativistic mean field approach. The analysis leads to potentials with a repulsive real part in the nuclear interior. The data are sufficient to establish the size of the isovector meson-hyperon coupling. Implications to Σ hypernuclei are discussed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
146
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(154 citation statements)
references
References 45 publications
8
146
0
Order By: Relevance
“…It has been shown that the experimental data is compatible with the analysis by the Nijmegen model F for the baryon-baryon interaction, which gives a repulsive isoscalar part and a large positive isospin dependent term (Lane potential) for the Σ-nucleus potential [78]. The analysis of Σ − atom data also shows the repulsive Σ − potential [80]. Theoretically, a repulsive Σ potential in nuclear matter has been obtained from the G matrix calculation based on the SU(6) quark model baryon-baryon interaction [81].…”
Section: Potential Contributionsupporting
confidence: 58%
“…It has been shown that the experimental data is compatible with the analysis by the Nijmegen model F for the baryon-baryon interaction, which gives a repulsive isoscalar part and a large positive isospin dependent term (Lane potential) for the Σ-nucleus potential [78]. The analysis of Σ − atom data also shows the repulsive Σ − potential [80]. Theoretically, a repulsive Σ potential in nuclear matter has been obtained from the G matrix calculation based on the SU(6) quark model baryon-baryon interaction [81].…”
Section: Potential Contributionsupporting
confidence: 58%
“…For Σ hyperons, it is necessary to analyze continuum spectra. In the observed (quasi-)bound Σ nucleus Σ − -nucleus potential having a shallow attractive pocket around the nuclear surface and repulsion inside the nucleus [34,35,36], but the atomic energy shift is not sensitive to the potential inside the nucleus. In the distorted wave impulse approximation (DWIA) analyses of the quasi free (QF) spectrum in the continuum region [20,21,22,23], it is suggested that the Σ hyperon would feel repulsive real potential of 10 ∼ 90MeV.…”
Section: Relativistic Mean Field Model With Hyperonsmentioning
confidence: 87%
“…Let us consider the elastic scattering of − hyperons from 28 Si [9,31]. We calculate the angular distributions of the differential cross section in this elastic scattering, using several types of the -nucleus potential (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The latest analyses of the − atomic x ray have suggested that the -nucleus potential has a repulsion inside the nuclear surface and a shallow attraction outside the nucleus with a sizable absorption [6,[8][9][10][11]. Noumi and his collaborators [12,13] have performed measurements of hypernuclei by inclusive (π − , K + ) reactions on C, Si, Ni, In, and Bi targets at p π = 1.20 GeV/c in KEK-E438 experiments.…”
Section: Introductionmentioning
confidence: 99%